ANALISIS SISTEM PRESENSI BERBASIS GOOGLE APPS SCRIPT: STUDI KASUS TUTORIAL PAI-SPAI UPI - Ummara, Taufiq Wadi; Fahmi, I’zaz Dzul; Azis, Dwi Fauzan Muhammad; Arif, Wildan Zamaludin; Yulia, Hazza Erlina Putri; Hamidah, Siti (Elconika: Jurnal Teknik Elektro, 2025)
An optimal attendance system is required to accurately record student attendance, which will ultimately affect their final grades. In the mentoring segment of the PAI-SPAI UPI Tutorial, a Google Apps Script-based attendance system implementing the Haversine formula is used. This research aims to analyse the attendance system to identify any issues that may cause data inaccuracies, rendering the system ineffective. The study employs qualitative and quantitative approaches, utilizing interviews, observations, literature reviews, and experiments. The results show that out of 5 Android devices and 5 iOS devices tested, 2 Android devices and 1 iOS device encountered issues preventing them from recording attendance. Additionally, the system's location accuracy and consistency were only 44.82%, which falls under the "moderately accurate" category, though it is close to the threshold of being "less accurate" (<40%). The research also identified a data overwriting issue, where existing attendance data was erased and replaced by newly submitted data within an extremely short timeframe. As a result, some participants who had already marked their attendance were not recorded. In conclusion, the attendance system used in the mentoring segment of the PAI-SPAI UPI Tutorial is still not optimal or effective, necessitating further development to improve its performance.